Education, Citizenship, and Cuban Identity by Rosi Smith. - Smith, Rosi. (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2016)
This book explores how Cuba’s famously successful and inclusive education system has formed young Cubans’ political, social, and moral identities in a country transfigured by new inequalities and moral compromises made in the name of survival. The author examines this educational experience from the perspective of those who grew up in the years of economic crisis following the fall of the Soviet Union, charting their ideals, their frustrations and their struggle to reconcile revolutionary rhetoric with twenty-first century reality. .